Busca domiciliar no crime de tráfico de drogas segundo a jurisprudência dos tribunais superiores - PANTOJA, Carla Layla Santos (2024)
This paper addresses the impact of the superior courts' understanding of police entry into a home during a drug trafficking crime in the case of an arrest in flagrante delicto, highlighting the importance of the inviolability of the home. The research explores the concept of domicile, permanent crimes, and police actions, with an emphasis on the jurisprudence of the Federal Supreme Court (STF) and the Superior Court of Justice (STJ). Based on Extraordinary Appeal No. 603.616, Topic 280, there has been a reinforcement of the need for reasonable grounds for police entry, requiring concrete elements to justify the measure. However, the analysis identified divergences between the superior courts regarding the characterization of reasonable grounds, leading to legal uncertainty and practical challenges for police operations. The research also examines the legal consequences of violating the inviolability of the home, such as the illegality of evidence and procedural nullity, as well as the impact on the most vulnerable populations, who often suffer from abusive and selective actions. The methodology used was bibliographic and documentary research, covering legislation, jurisprudence, and data from official reports. Finally, it concludes that, although jurisprudential advances have promoted greater rigor in police actions, practice still reveals frequent violations of fundamental rights, suggesting the need for greater standardization of applicable criteria and training for public security officers.